Green hydroxyapatite-zeolite catalyst derived from steel waste as an effective catalyst for the hydrocarbon production via co-catalytic pyrolysis of sugarcane bagasse and high-density polyethylene - H., Hassan (2023)
Hydroxyapatite-zeolite (HAP-ZE) catalyst prepared from steel waste was utilised in co-catalytic pyrolysis of sugarcane bagasse (SB) and high-density polyethylene (HDPE) for bio-oil production. The highest bio-oil yield (71.19 wt%) was obtained at HAP-ZE to SB/HDPE ratio of 1:6, and mass ratio of SB to HDPE of 40:60. HAP-ZE favoured the production of hydrocarbon and alcohol and inhibited the production of acid. The acid sites promoted the hydrogenation and deoxygenation via hydrocarbon pool while the basic sites promoted the deoxygenation reactions via decarboxylation and decarbonylation. HAP-ZE large pores facilitates access of bulky pyrolyzates to active sites, promoting deoxygenation and hydrocarbons formation.